IN VITRO EVALUATION OF CHLOROQUINE AND CLARITHROMYCIN AGAINST LEISHMANIA TROPICA - Khan, Momin; Jan, Farzana; Khan, Imran; Zeb, Mubarak; Ullah, Ihsan (Journal of Postgraduate Medical Institute, 2021)
Objective: To evaluate the efficacy of already registered drugs chloroquine and clarithromycin against Leishmania tropica KWH 23. Methodology: This experimental study was conducted at the Institute of Basic Medical Sciences, Khyber Medical University Peshawar, Pakistan. Pre-established cultures of Leishmania tropica KWH23 were inoculated in Roswell Park Memorial Institute (RPMI) 1640 Medium and incubated at 24ºC for 7 days. Stock solution of chloroquine and clarithromycin of 1000 µg/ml were prepared and were further diluted serially. Approximately, 180 µl of RPMI was added in different wells of 96 well microtiter plates. For the test compound, 20 µl was added in the first well and then serially diluted, to keep the final volume up to 180 µl. subsequently 20 µl was discarded from the last well. About 100 µl of parasites (2í—106 cells/ml were added in each well and 2 rows were left for positive and negative control. Dimethyl sulfoxide (DMSO) was taken as negative control and serially diluted in RPMI 1640 medium. Amphotericin B was taken as positive control. Microtiter plates were incubated at 24oC for 72 hours. Assay was performed in triplicate. After the incubation period, 20 µl was taken from each dilution and put on improved Neubaur counting chamber and live parasites were counted under microscope. IC50 values of the compounds possessing anti leshmanial activity were calculated by GraphPad Prism 5 software. Results: The IC50 values of chloroquine dosage and pure forms (without excipients) against the promastigote of Leishmania tropica KWH23 were 0.023µg/ml and 0.019 µg/ml respectively while IC50 values of clarithromycin dosage and pure form were 4.548 µg/ml and 27.13 µg/ml respectively. Clarithromycin inhibited promastigotes growth but its IC50 is higher than chloroquine. The IC50 values of combination of chloroquine and clarithromycin dosage (500 mg) and pure form were recorded as 0.049 µg/ml and 0.0023 µg/ml respectively. Conclusion: These results show that both chloroquine and clarithromycin are potential candidate drugs for the treatment of cutaneous leishmaniasis.